Who-Man: Redefinisi Konsep Manusia dan Teknologi dalam Terang Pemikiran Jean-Francois Lyotard - Revie Marthensa (Parahyangan Catholic University, 2020)
Technology continues to develop over time, from the Stone Age to the present day. Humans originally were the subject of creators and users of technology now feel threatened because they have degenerated into simply objects to technology. In other words, human dignity itself is threatened. According to Jean-François Lyotard, it can even be said of humans that we too are some form of technology, technology consisting of intelligent organ systems which have certain functioning mechanisms and that which work together to form an individual. Humans can not claim to be the most dignified of all creatures; we are but technological beings, motes of a much grander technological universe. Everything that which humanity creates and strives for, such as that of tech- nology, comes into its existence solely not of our own merits of skill or dignity, but rather due to humanities role as participants of a moving universe.